PEMANFAATAN MEDIA SOSIAL FACEBOOK SEBAGAI MEDIA PENYAMPAIAN MATERI AJAR BAGI PESERTA DIKLAT DI BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (BP2IP) BAROMBONG - Kusmaladi, Rony; Haanurat, Ifayani (COMPETITIVENESS, 2019)
AbstractThis study aims to find out the use of Facebook social media as a medium of delivery of teaching materials, where activities in the form of delivery of teaching materials, namely uploading material with various types of files (documents, pdf, images, videos), discussions / comments, assignments and workmanship, and online replays. The informants in this study consisted of Improvement Training Participants and Instructors, both instructors who have used Facebook social media as a medium of delivery of teaching materials, and who have not utilized them. The research was conducted starting in July 2018 and ending in December 2018. This research uses qualitative approach, data collection using observation method, interview, and documentation. The results showed that instructors responded positively to the use of Facebook social media as a medium of delivery of teaching materials at BP2IP Barombong, they hope there are rules governing the use of Facebook social media. Those who have used Facebook as a medium of delivery of teaching materials, have not optimized the features on Facebook. Online replays that can be easily applied with Facebook are also still minimal in utilization. Instructors are bothered when they have to type multiple choice questions online, they prefer to give questions / assignments in the form of essays to be done by training participants and send them in the comment box on Facebook. Training participants are very enthusiastic about online learning and replays, especially when instructors are unable to attend teaching. They hope all lessons can be utilized on Facebook social media as a medium of delivery of teaching materials. Keywords: Facebook social media, teaching material media, online replays.